A diverse group of small circular ssDNA viral genomes in human and non-human primate stools. Issue 1 (31st December 2015) - Ng, Terry Fei Fan; Zhang, Wen; Sachsenröder, Jana; Kondov, Nikola O.; da Costa, Antonio Charlys; Vega, Everardo; Holtz, Lori R.; Wu, Guang; Wang, David; Stine, Colin O.; Antonio, Martin; Mulvaney, Usha S.; et al.
Abstract : Viral metagenomics sequencing of fecal samples from outbreaks of acute gastroenteritis from the US revealed the presence of small circular ssDNA viral genomes encoding a replication initiator protein (Rep). Viral genomes were ∼2.5 kb in length, with bi-directionally oriented Rep and capsid (Cap) encoding genes and a stem loop structure downstream of Rep. Several genomes showed evidence of recombination. By digital screening of an in-house virome database (1.04 billion reads) using BLAST, we identified closely related sequences from cases of unexplained diarrhea in France. Deep sequencing and PCR detected such genomes in 7 of 25 US (28 percent) and 14 of 21 French outbreaks (67 percent). One of eighty-five sporadic diarrhea cases in the Gambia was positive by PCR. Twenty-two complete genomes were characterized showing that viruses from patients in the same outbreaks were closely related suggesting common origins. Similar genomes were also characterized from the stools of captive chimpanzees, a gorilla, a black howler monkey, and a lemur that were more diverse than the human stool-associated genomes. The name smacovirus is proposed for this monophyletic viral clade. Possible tropism include mammalian enteric cells or ingested food components such as infected plants. No evidence of viral amplification was found in immunodeficient mice orally inoculated with smacovirus-positive stool supernatants. A role for smacoviruses in diarrhea, if any, remains to be demonstrated.